2008
DOI: 10.1088/0004-637x/690/2/1463
|View full text |Cite
|
Sign up to set email alerts
|

A Disk of Young Stars at the Galactic Center as Determined by Individual Stellar Orbits

Abstract: We present new proper motions from the 10 m Keck telescopes for a puzzling population of massive, young stars located within 3. 5 (0.14 pc) of the supermassive black hole at the Galactic center. Our proper motion measurements have uncertainties of only 0.07 mas yr −1 (3 km s −1 ), which is 7 times better than previous proper motion measurements for these stars, and enables us to measure accelerations as low as 0.2 mas yr −2 (7 km s −1 yr −1 ). Using these measurements, line-of-sight velocities from the literat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
458
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(519 citation statements)
references
References 75 publications
40
458
10
Order By: Relevance
“…Current observations favor in situ formation based on the steep fall off in the number of young disk stars at larger radii. The observed radial density profile is consistent with ρ(r) ∝ r −2 as predicted for in situ gas disks and is much steeper than the ρ(r) ∝ r −0.75 predicted for in-falling cluster scenarios (Lin & Pringle 1987;Berukoff & Hansen 2006;Levin 2007;Lu et al 2009;Bartko et al 2009). The simplest in situ formation scenarios initially produce circular orbits since gas that flows in at low or moderate rates circularizes prior to the onset of star formation (Nayakshin & Cuadra 2005;Alexander et al 2007;Löckmann et al 2009).…”
Section: The Young Nuclear Clustersupporting
confidence: 84%
See 2 more Smart Citations
“…Current observations favor in situ formation based on the steep fall off in the number of young disk stars at larger radii. The observed radial density profile is consistent with ρ(r) ∝ r −2 as predicted for in situ gas disks and is much steeper than the ρ(r) ∝ r −0.75 predicted for in-falling cluster scenarios (Lin & Pringle 1987;Berukoff & Hansen 2006;Levin 2007;Lu et al 2009;Bartko et al 2009). The simplest in situ formation scenarios initially produce circular orbits since gas that flows in at low or moderate rates circularizes prior to the onset of star formation (Nayakshin & Cuadra 2005;Alexander et al 2007;Löckmann et al 2009).…”
Section: The Young Nuclear Clustersupporting
confidence: 84%
“…The observed eccentricity distribution peaks at e=0.3 Yelda et al 2013). Scenarios invoking more rapid gas inflow, such as the infall of a single molecular cloud or the collision of two molecular clouds, could produce disk stars with large initial eccentricities and have the added bonus of producing a large population of young stars off the disk (Bonnell & Rice 2008;Wardle & Yusef-Zadeh 2008;Hobbs & Nayakshin 2009;Mapelli et al 2012), similar to what has been observed (Paumard et al 2006;Bartko et al 2009;Lu et al 2009;Yelda et al 2013). However, the evolution of an initially circular disk over 4-6 Myr depends on the initial mass function (IMF) of the stars and it is possible to evolve to today's observed distribution for moderately top-heavy IMFs .…”
Section: The Young Nuclear Clustersupporting
confidence: 77%
See 1 more Smart Citation
“…As displayed in Figures 4(b), (c), RS5 and RS6 have near-IR counterparts. Although there is an early-type star, S1-22, that may be associated with RS6, RS5 is not identified as a near-IR star in various catalogs (e.g., Lu et al 2009Lu et al , 2013. There is no evidence for a known young and massive star associated with RS5.…”
Section: Proplyd Candidates Near Sgr a * ?mentioning
confidence: 96%
“…To see if these stars have radio continuum counterparts, their positions at the epoch of our 34 GHz observation on 2014 March 9 (2014.19) have been calculated based on proper motions and orbital accelerations have been derived from near-IR observations (Lu et al 2009;Gillessen et al 2009;Yelda et al 2014). Tables 2 and 3 give the positions of the S-cluster and their corresponding positional uncertainties at the epoch of 2014.19 and from two different catalogs (Gillessen et al 2006;Lu et al 2009). Table 4 Table 5 lists Gaussian-fitted positions of 8 radio sources (RS1-8) embedded within the diffuse extended emission associated with the Sgr A * ridge and the plume-like structure at 34 GHz (see Figures 1 and 2).…”
Section: Radio Emission From the S Clustermentioning
confidence: 99%